High Hydrostatic Pressure Induces a Lipid Phase Transition and Molecular Rearrangements in Low‐Density Lipoprotein Nanoparticles. (18th July 2018) - Lehofer, Bernhard; Golub, Maksym; Kornmueller, Karin; Kriechbaum, Manfred; Martinez, Nicolas; Nagy, Gergely; Kohlbrecher, Joachim; Amenitsch, Heinz; Peters, Judith; Prassl, Ruth
Abstract: Low‐density lipoproteins (LDL) are natural lipid transporter in human plasma whose chemically modified forms contribute to the progression of atherosclerosis and cardiovascular diseases accounting for a vast majority of deaths in westernized civilizations. For the development of new treatment strategies, it is important to have a detailed picture of LDL nanoparticles on a molecular basis. Through the combination of X‐ray and neutron small‐angle scattering (SAS) techniques with high hydrostatic pressure (HHP) this study describes structural features of normolipidemic, triglyceride‐rich and oxidized forms of LDL. Due to the different scattering contrasts for X‐rays and neutrons, information on the effects of HHP on the internal structure determined by lipid rearrangements and changes in particle shape becomes accessible. Independent pressure and temperature variations provoke a phase transition in the lipid core domain. With increasing pressure an interrelated anisotropic deformation and flattening of the particle are induced. All LDL nanoparticles maintain their structural integrity even at 3000 bar and show a reversible response toward pressure variations. The present work depicts the complementarity of pressure and temperature as independent thermodynamic parameters and introduces HHP as a tool to study molecular assembling and interaction processes in distinct lipoprotein particles in a nondestructive manner. Abstract : High hydrostatic pressure induces a lipid phase transition and a reversible anisotropic deformation of low density lipoprotein (LDL) nanoparticles, which are natural lipid transporter in human plasma. With increasing pressure an interrelated anisotropic deformation and flattening of the particle is induced, which is detected by neutron and X‐ray small angle scattering techniques.